2001
DOI: 10.1021/cc000096t
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Maximally Diverse and Druglike Screening Library Using REM Resin Methodology

Abstract: A 3042 compound screening library was synthesized using a combination of two solid-phase technologies: REM resin methodology and Lewis acid promoted aminolysis. The exclusivity and structural diversity of the library were enhanced by using a highly divergent synthetic strategy involving 13 different scaffolds (9 of which were custom-made), five different types of resin-bound phenol derivatization chemistry (Mitsunobu, Suzuki, acylation, sulfonylation, and carbamoylation), and three different cleavage strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…It was concluded that orally active drugs with passive transcellular transport should not exceed a PSA of 120 Å 2 , and a 60-70 Å 2 for appropriate BBB permeability. MW was identified as a good descriptor of BBB penetration [66,67], and applied in fact as a key property filter together with logP in testing a 3042 compound screening library [68] for CNS-compatibility. Chico et al [69] claimed that kinase inhibitor drugs for CNS indications required a modification of the property limits set by the Ro5.…”
Section: Specific Drug-likenessmentioning
confidence: 99%
“…It was concluded that orally active drugs with passive transcellular transport should not exceed a PSA of 120 Å 2 , and a 60-70 Å 2 for appropriate BBB permeability. MW was identified as a good descriptor of BBB penetration [66,67], and applied in fact as a key property filter together with logP in testing a 3042 compound screening library [68] for CNS-compatibility. Chico et al [69] claimed that kinase inhibitor drugs for CNS indications required a modification of the property limits set by the Ro5.…”
Section: Specific Drug-likenessmentioning
confidence: 99%
“…an increased likelihood of the compounds to cross the BBB [72]. Organon, for example, have published an interesting approach for the design of an information-rich library involving state-of-the-art knowledge on computational tools to predict CNS penetration, which was the basis for the purpose-built synthesis of an HTS compound library privileged for CNS programs [73]. The ongoing process of refining the computational approaches to the prediction of CNS penetration and blood-brain distribution [74][75][76][77][78][79][80][81][82][83][84][85][86][87] will be the way forward to a more successful virtual screening and design of CNS-like compound libraries.…”
Section: Cns Programsmentioning
confidence: 99%
“…General procedure for the Suzuki reaction using triflates [121]: The following procedure employs K 2 CO 3 , which may cause hydrolysis of labile esters within the coupling components.…”
Section: Methodsmentioning
confidence: 99%
“…These mixtures of solids can then be distrib- Merrifield [95] Br Ph, Ph with EDG in 2-and 3-positions, 3-thiophenyl, 2-thiophenyl 0.05 equiv. Pd(PPh3) 4 Boronate resin [55] REM resin [121] Ph with EWG and EDG in 2, 3, 4 position 4 equiv. Ph with EWG in 2, 3, and 4-positions; EDG in 4-or 2-position of naphthyl 0.1 equiv.…”
mentioning
confidence: 99%